Immunoglobulin secretion by B1 cells: Differential intensity and IRF4-dependence of spontaneous IgM secretion by peritoneal and splenic B1 cells - Holodick, Nichol E. (2010)
Peritoneal B1 cells are typified by spontaneous, constitutive secretion of IgM natural antibody, detected by ELISPOT assay, among other means. Recently, this key characteristic has been called into question, a reason for which we evaluated the integrity of IgM(+) ELISPOT spots. We found that fixed B1 cells fail to produce ELISPOT spots, that interference with Golgi function inhibits ELISPOT spot formation, and that B1 cell-derived immunoglobulin in supernatant samples is EndoH-resistant. These findings indicate that spots produced by B1 cells on ELISPOT assay reflect secretory IgM actively exported by viable B1 cells. Current paradigms propose that interferon response factor 4 (IRF4) is required for plasma cell differentiation and immunoglobulin secretion. However, we found that IgM secretion by peritoneal B1 cells is not altered in IRF4-null mice. In contrast, spontaneous IgM secretion by splenic B1 cells, which amounts to much more IgM secreted per cell, is dramatically reduced in the absence of IRF4. These results indicate that peritoneal B1 cells spontaneously secrete low levels of IgM via an IRF4-independent non-classical pathway, and, considering the low level of serum IgM in IRF-null mice, further suggest that accumulation of serum immunoglobulin depends on IRF4-dependent secretion by splenic B1 cells.